PSYCHOLOGICAL ASPECTS OF DISTANCE LEARNING IN SECONDARY SCHOOLS: A STUDY BASED ON FOREIGN RESEARCH EXPERIENCE (Psychology Travelogs, 2025)
This paper examines the psychological dimensions of distance learning in secondary education, focusing on motivation, self-regulated learning, stress and well-being as well as social connectedness. Drawing on recent empirical and theoretical studies, it explores how remote formats challenge adolescents’ psychological needs and developmental trajectories. As the present article relies exclusively on international research, it highlights global trends that can be instructive for improving distance education practices more broadly. The paper discusses mechanisms to support students – such as scaffolding self-regulation, fostering belonging, and providing emotional support – and proposes implications for educators and policymakers. Finally, it outlines limitations and offers directions for future research.
Keywords: distance learning; secondary education; adolescent psychology; motivation; self-regulated learning; mental health